New media adoptions and organisational citizenship behaviours among corporate communication practitioners / Wardatul Hayat Adnan - Adnan, Wardatul Hayat (Institute of Graduate Studies, UiTM, 2018)
Industry 4.0 is a name for the current trend of an automation and data exchange in manufacturing technologies. It includes cyber-physical systems the internet of things (IoT), cloud computing and cognitive computing. The readiness of the people in organisation is at critical stage in order to run the organisation smoothly. This study aims to explore the acceptance and use of new media among corporate communication practitioners and to examine the influence on organizational citizenship behaviour. The study employs quantitative methodology of cross sectional - correctional survey. A set of questionnaires containing 4 sections measuring all instruments in the study were conducted on 268 corporate communication practitioners. Off 268, 62 males and 206 females selected using stratified random sampling among corporate communication practitioners working with MNC's in Malaysia. For data analysis, SPSS statistical software was utilized for preliminary data processing and Structural Equation Modelling (SEM) of AMOS was used for exploratory data analysis and multi-correlational analysis. There are 16 hypotheses developed in the study. All hypothesis is accepted due to its significance. However, further findings lead to 3 constructs to be dropped due to its fitness in full CCNA model [NMEE, CCSB & OCB]…